Osteuropäisch – jüdisch – sozialistisch : Untersuchung einer vergessenen Berliner Exilgruppe der Weimarer Republik - Stürmann, Jakob (Europäisch-jüdische Studien – Beiträge, 2022)
This study sheds light on the lives of an exiled group of Eastern European Jewish socialists who spent time in Berlin during the Weimar Republic, analyzes the different ways that they understood belonging, and traces their interactions with the international labor movement. It investigates in detail the exiles’ intermediary function between East and West, and between the non-Jewish and Jewish Socialist labor movements